"Confronting [the shooter] could save your life…or end it": school lockdowns and the blending of pastoral care with risk management. Issue 3 (4th May 2022) - Levinsky, Zachary
ABSTRACT: Lockdowns have become a ubiquitous solution to the problems posed by school safety and dealing with an active shooter. However, the emergence of this new technique has not been adequately discussed or theorized. The present article will address this gap by using a school board in Canada as an empirical site to map out how the turn to risk management practices, such as the lockdown, are situated within the pastoral and compassionate dreams of a liberal education system. I argue the lockdown changes the way school safety is understood and shifts the politics of blame and accountability. However, the duty of care of schools and educators has implications for how this risk management strategy is enacted.